Primeiras viagens de S. Josemaría a Portugal (1945) / Josemaría’s First Journeys to Portugal (1945) - Hugo de Azevedo (Studia et Documenta)
The author describes St. Josemaría’s first journey to Portugal, made following Sister Lucia of Jesus’ request, to make Opus Dei known to several Portuguese bishops. As a result of these meetings, and of the international state of affairs, St. Josemaría changes his plans for apostolic expansion and decides to begin apostolic work in Portugal. The author tells of three other such journeys to Portugal in 1945, and of the decision to open a centre of Opus Dei in Coimbra; he also relates the preparative work which went into the Portuguese translation of The Way.